2020
DOI: 10.3389/fgene.2020.00954
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Prevalence Studies and Familial Aggregation in Vestibular Migraine

Abstract: Background: Vestibular migraine (VM) is complex disorder consisting of episodes of migraine and vertigo with an estimated prevalence of 1-3%. As migraine, it is considered that VM has genetic predisposition; however, evidence to support a genetic contribution has not been critically appraised. Objective: The aim of this systematic review is to assess available evidence in scientific publications to determine the role of inheritance in VM. Methods: After performing the quality assessment of the retrieved record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 52 publications
0
16
1
1
Order By: Relevance
“…Finally, the familial history of auditory or vestibular symptoms was not obtained in the present study. However, both VM and MD show a significant familial aggregation (41,42), and families with either VM or MD may have individuals with partial syndromes that could fit in the diagnosis of RVS-NOS. Future studies should investigate familial aggregation of RVS-NOS and VM.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Finally, the familial history of auditory or vestibular symptoms was not obtained in the present study. However, both VM and MD show a significant familial aggregation (41,42), and families with either VM or MD may have individuals with partial syndromes that could fit in the diagnosis of RVS-NOS. Future studies should investigate familial aggregation of RVS-NOS and VM.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Of the studies >50%, one reported vestibular migraine and one reported menstrual migraine. General population VM prevalence is estimated between 1 and 3% (Paz‐Tamayo et al, 2020), whilst MM affects about 20‐25% of female migraineurs (Vetvik & MacGregor, 2021). Potential reasons for the >50% prevalence rates in the studies within the current review include financial incentivization and a self‐report survey via Facebook (Abouzari et al, 2020), and in Tavares et al, 2021; inclusion of females at the peak of reproductive age (18–28 years old).…”
Section: Discussionmentioning
confidence: 99%
“…In both familial and non-familial cases of VM, there was a female predominance in most of the studies included in systematic review [13]. The mean age of onset of VM in patients with concurrent migraine and vertigo manifestation was found to be 22.7 ± 10.4 years, whereas patients with a non-simultaneous presentation of symptoms were somewhat older, with a mean age of onset for vertigo of 35.6 ± 12.4 years and 24 ± 8.9 years for migraine [18].…”
Section: Epidemiology and Comorbiditymentioning
confidence: 99%